The cultivation of vorstenlands tobacco in Surakarta resdency and Besuki tobacco in Besuki residency and its impact on the peasant economy and society : 1860-1960 - Sugiyanto Padmo (Aditya Media, 1994)
ast c.1-4/ast c.5